2016
DOI: 10.1080/09506608.2016.1219481
|View full text |Cite
|
Sign up to set email alerts
|

Graphene reinforced metal and ceramic matrix composites: a review

Abstract: This review critically examines the current state of graphene reinforced metal (GNP-MMC) and ceramic matrix composites (GNP-CMC). The use of graphene as reinforcement for structural materials is motivated by their exceptional mechanical/functional properties and their unique physical/chemical characteristics. This review focuses on MMCs and CMCs because of their technological importance for structural applications and the unique challenges associated with developing high-temperature composites with nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
198
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 501 publications
(222 citation statements)
references
References 217 publications
2
198
1
4
Order By: Relevance
“…The theoretical λ value of graphene is approximately 5300 W/mK, representing promising application as thermally conductive films and composites [150][151][152][153][154]. Zhao and coworkers [155] successfully fabricated the poly(p-phenylene benzobisoxazole) (PBO)-based nanocomposite film (λ value of 50 W/mK in the in-plane direction) with 5 wt% thermally reduced graphene sheets (TRG).…”
Section: Carbon-based Fillersmentioning
confidence: 99%
“…The theoretical λ value of graphene is approximately 5300 W/mK, representing promising application as thermally conductive films and composites [150][151][152][153][154]. Zhao and coworkers [155] successfully fabricated the poly(p-phenylene benzobisoxazole) (PBO)-based nanocomposite film (λ value of 50 W/mK in the in-plane direction) with 5 wt% thermally reduced graphene sheets (TRG).…”
Section: Carbon-based Fillersmentioning
confidence: 99%
“…Achieving the uniform dispersion of graphene in metal matrix is the key challenge in the practical development of graphene/metal composites, because graphene tends to form agglomerates in the fabrication process due to its nano‐scale dimension and enormous surface area . Currently, much effort has been devoted to addressing the graphene distribution issue and some success has been attained . Ball milling still remains the most popular method to disperse graphene in different metal powders, because it is easy to operate, cost effective, and widely applicable to various metals .…”
Section: Introductionmentioning
confidence: 99%
“…The graphene‐metal interface, however, is known to be naturally weak due to the poor interface wettability originating from the large mismatch in surface tension between the graphene and metal matrix . One solution to overcome this problem is to precoat the metal/carbide coatings on the surface of graphene owing to the fairly good chemical affinity of coatings to both graphene and Cu matrix . Tang et al reported that the use of Ni‐coated RGO could improve both the graphene dispersion and the interface adhesion with Cu matrix, leading to a 94% enhancement in yield strength compared to pure Cu.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum temperature used during sintering was of 500 • C with a holding time of 10 min. These parameters were selected based on experience with previous study [19]. A heating rate of 50 • C/min in a vacuum was used.…”
Section: Spark Plasma Sintering (Sps)mentioning
confidence: 99%